Windows Vista Ultimate Bible - Torres Derek (Wiley, 2007)
If you're the ultimate gamer and multimedia fan, Windows Vista Ultimate and this information-packed book are for you. Want to launch games with a single click? Share files with your Xbox 360? Try out new audio and media tools? It's all here and then some. You'll find step-by-step tutorials, techniques, and hacks—plus in-depth discussions of games, gaming, performance tips, and much more. Whether you're a veteran Windows gearhead or just getting started, this is the book you need to succeed with Vista Ultimate.